Trends in Supersonic Separator design development - Altam, R.A. (EDP Sciences, 2017)
Supersonic separator is a new technology with applications in hydrocarbon dew pointing and gas dehydration which can be used to condensate and separate water and heavy hydrocarbons from natural gas. Many researchers have studied the design, performance and efficiency, economic viability, and industrial applications of these separators. The purpose of this paper is to succinctly review recent progress in the design and application of supersonic separators and their limitations. This review has found that while several aspects of this study are well studied, considerable gaps within the published literature still exists in the areas such as turndown flexibility which is a critical requirement to cater for variation of mass flow and since almost all the available designs have a fixed geometry and therefore cannot be considered suitable for variable mass flow rate, which is a common situation in actual site. Hence, the focus needs to be more on designing a flexible geometry that can maintain a high separation efficiency regardless of inlet conditions and mass flow variations. This review is focusing only on the design and application of the supersonic separators without going through the experimental facilities, industrial platform, pilot plants as well as theoretical, analytical, and numerical modelling. © The authors, published by EDP Sciences, 2017.